THE ROLE OF CONTEXT IN INTERPRETING MEANING: A SEMANTIC STUDY - Sintya Margaretta Sinaga; Bernieke Anggita Ristia Damanik (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study investigates how context shapes the interpretation of meaning in language from a semantic perspective. While traditional semantics often focuses on the relationship between linguistic forms and their inherent meanings, this research emphasizes that meaning cannot be fully understood without considering contextual factors. The study aims to explore how different types of context—linguistic, situational, and cultural—interact to influence meaning construction and interpretation. Using a qualitative descriptive approach, the research analyzes selected examples from both written and spoken discourse to identify how context contributes to meaning disambiguation and pragmatic understanding. The findings demonstrate that context plays a decisive role in resolving lexical and structural ambiguity, guiding inference, and aligning interpretation with speaker intention. In particular, the study highlights that identical linguistic expressions may yield different meanings depending on contextual conditions. The study concludes that context is not a peripheral element but a central component in semantic interpretation. Incorporating contextual analysis enhances the accuracy of meaning interpretation and supports more effective communication. These findings have important implications for linguistic theory, language teaching, translation studies, and discourse analysis, where sensitivity to context is essential for achieving clarity and precision.